Aplikasi E–Commerce Toko Sinar Bella dengan Metode Rapid Application Development (RAD) menggunakan Framework CodeIgniter 4 - Riza Dwi Atmaja; NM Faizah; Maspul Aini Kambry (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
With the rapid development of online business, there has been a lot of competition in the online shop industry in Indonesia, for example, the potential for e-Commerce growth is very good, there are lots of online shop companies that are developing, each of which has its own concept and characteristics. E-Commerce based on online stores cannot be separated from websites. E-Commerce provides an easy way to sell and buy products and information via the internet or other means. Websites provide great benefits for internet users, especially online business people, to develop their business. research objectives are; Designing an e-Commerce web-based sales application, Designing an online Store Goods sales application, and Making it easier for buyers to make payments at Sinar Bella stores. In the application development process using the Rapid Application Development (RAD) method while the Unified Modeling Language (UML) is a representation in the application design later and CodeIgniter 4 as a framework in building applications. The results of the research that; The design and implementation of creating a website at the Sinar Bella store is the availability of a customer service system, with the Sinar Bella website being a media provider for delivering information and website-based sales, the design of this website is aimed at the wider community, especially internet users, so that they can easily purchase products online.